DESIGN USER INTERFACE DESIGN AND USER EXPERIENCE IN SIAKAD APPLICATION USING USER CENTERED DESIGN (UCD) METHOD IN ISLAM UNIVERSITY COUNTRY SUNAN AMPEL SURABAYA - Ahmad iqbal yunus; Sulistyowati Sulistyowati; Tan Amelia (Jurnal Sistem Informasi Universitas Dinamika, 2018)
SIAKAD is a web-based academic information system application with the aim of providing academic information to students. With SIAKAD students can find information related to academic campus such as student biography, IAIN publications, class forums, messages, curriculum majors, semester courses, Study Plan Card (KRS), college schedule, attendance, thesis, yudisium form, student consultation, Study Result Card (KHS), learning progress, value list, transcript, repeat history, and finance. The number of visitors SIAKAD application every month is different - different, sometimes up sometimes down because of the information contained in SIAKAD less complete. In addition, the user interface/user experience is less interesting. The solution to this problem is to design user interface/user experience with User Centered Design method which consists of understanding and defining user context, specifying user requirements, creating user interface design, evaluating user results.